(untitled) (International Journal of Engineering and Computer Science, 2015)
Analyzing logs of a network can help us extract important information about users and the usage of network bandwidth. This information can then be used by the network administrator to take necessary administrative actions in order to enhance the security of network. There are several log analyzers available in the market, but have limited features or are platform dependent. In this paper, an efficient and platform independent log analyzer is proposed. This log analyzer along with all essential features regarding users, traffic and bandwidth usage, also has inbuilt features for search engine analysis and contains searched keywords and phrases in its reports. These reports give a easy-to-understand view of bandwidth usage by different users and also the type of content the users are accessing. The searched keywords and phrases report gives an idea about what is being searched on the network. The network administrator, who has the ability to filter users and traffic on the network can then take necessary steps to ensure that the network security policy of the organization remains intact. This also gives the network administrator flexibility, in taking decisions regarding maintaining the security of network. This log analyzer also overcomes issues faced in other tools by procuring reduced memory consumption and by being platform independent.